Voluntary Sustainability Standards (VSS) and the "greening" of high-emitting industry sectors in Brazil: Mapping the sustainability efforts of the private sector - Vera Thorstensen; Ariel Macaspac Hernandez; Rogerio de Oliveira Corrêa; Dolores Teixeira de Brito; Mauro Kiithi Arima Júnior; Catherine Rebouças Mota; Tiago Matsuoka Megale; Amanda Mitsue Zuchieri; Fábio Jorge Thomazella (German Institute of Development and Sustainability (IDOS), 2024)
The work aimed to analyse the sustainability efforts - the greening - of five industry sectors in Brazil: aluminium, chemical, steel, cement, and oil and gas. These sectors were chosen because they are the industries with the highest carbon emissions. The research sought to verify the sustainability measures adopted by business and industry actors, with special emphasis on the use of Voluntary Sustainability Standards and ESG values. In order to verify the information provided by the companies, the documents that informed the measures taken by the companies and the numbers supporting their results were always sought out and explained in the text. The conclusions were that the sectors, guided by industry associations, have adopted a broad set of sustainability measures. The results of these measures, however, sometimes lack proof and sometimes lead to sporadic conduct, contrary to the precepts of environmental and social sustainability.
Keywords: 320; sustainable development goals; greening; green transition; transformation to sustainability; voluntary sustainability standards; ESG; quality infrastructures; high emitting industry sectors; Brazil